2020
DOI: 10.1186/s12902-020-00552-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lifestyle modifications on anthropometric, clinical, and biochemical parameters in adolescent girls with polycystic ovary syndrome: a systematic review and meta-analysis

Abstract: Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of childbearing age. This study aimed to compare the effects of lifestyle interventions on anthropometric, clinical, and biochemical parameters in adolescent girls with PCOS. Methods: PubMed, Scopus, and Web of Science was systematically searched to retrieve studies investigating the effects of lifestyle modifications in adolescent girls with PCOS, which were published up to December 2019. The primary outcome was Body M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 59 publications
3
45
0
1
Order By: Relevance
“…The current study is in agreement with study done by Abdolahian, et al, [1] who studied the effect of lifestyle modifications on anthropometric, clinical, and biochemical parameters in adolescent girls with PCOS in Iran and revealed that, exercise interventions were associated with significant changes in the menstrual cycles, also improvement in metabolic and hormonal findings.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study is in agreement with study done by Abdolahian, et al, [1] who studied the effect of lifestyle modifications on anthropometric, clinical, and biochemical parameters in adolescent girls with PCOS in Iran and revealed that, exercise interventions were associated with significant changes in the menstrual cycles, also improvement in metabolic and hormonal findings.…”
Section: Discussionsupporting
confidence: 93%
“…Table (1): Reveals that, more than two third of the studied sample (73.5%) had age ranged between 18-20 years with mean age 19.89 years, more than one third grade had 2nd grade, more than half of students' lives in city ,and the majority of the studied sample (80.9%) lives in the nucleolus family. Also, half of the studied sample had educated mothers at the secondary level, while (44.1%) of them had educated fathers at the university level.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The genetic predisposition [ 95 , 96 , 97 , 98 ] and epigenetic factors, including an increased level of gene methylation, histone modification, and microRNA pattern variation [ 99 , 100 , 101 ], are important for the development of PCOS. Environmental and socioeconomic factors are also of great importance, including ethnic characteristics, nutrition, and adverse environmental factors (toxins, xenobiotics, chemical mutagens, and ionizing radiation) [ 102 , 103 , 104 ]. The development of PCOS in women largely depends on the effects of maternal hormones during the prenatal period, as well as on their metabolic and hormonal status in the early childhood [ 84 , 99 , 105 , 106 , 107 ].…”
Section: Metformin and Polycystic Ovary Syndromementioning
confidence: 99%
“…Several treatments are recommended for PCOS such as life style modi cation (6), drug therapy (7) and herbal medicine (8).…”
mentioning
confidence: 99%